AGE AND PARITY RELATIONSHIP WITH MOTHER MATERNITY EVENT INTRAUTERINE FETAL DEATH (IUFD) ARIFIN ACHMAD HOSPITAL PROVINCE IN THE YEAR 2013 RIAU - sari, Sumia Arsita (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Indonesia is the fourth largest country in the world after China. In response to this, thegovernment has promoted a Family Planning Program (KB) which is a basic and primarypreventive health service to create a healthy and prosperous family. Based on the KBRecapitulation Program of the Pekanbaru City Health Office in October-December 2011from 19 Puskesmas, the highest use of implants was at Harapan Raya Health Center whichwas actually 245 acceptors, while the lowest Puskesmas used Implants at the Melur HealthCenter which is 0 acceptors. WUS with the selection of Implant contraceptives at theMelur Pekanbaru Health Center in 2012. This type of research is quantitative, withanalytical design. The population in this study were all WUS who used KB as many as 165acceptors. Sampling was carried out using 44 WUS Accidental Sampling Techniques. Thedata used were primary data. This research was carried out at the Melur Health Center onMarch 25-April 20, 2012. This research instrument used a questionnaire that had beentested for validity and reliability. Data processing by Editing, Coding, Processing, andCleaning. Data analysis was carried out by univariate and bivariate methods. Results of thestudy After statistical tests on the knowledge of WUS with the selection of implantsobtained results (P) 0.814> 0.05 = Ha was rejected and it can be concluded that there is norelationship between knowledge of WUS with the selection of implants. WUS educationwith implant selection results (P) 0.861> 0.05 = Ha rejected and it can be concluded thatthere is no relationship between WUS education and implant selection. Thus it is expectedthat health workers to further improve in providing clear information to the community,especially in women of childbearing age so as not to reduce their motivation to use implantcontraceptives.Keywords : Knowledge, Education, Implant Selection